Pengenalan dan Pelatihan Teknologi Rapid Prototyping Menggunakan 3D Printing di SMA Muhammadiyah 10 Sugio Lamongan - Rohmat Rohmat; Dianda Aryntya Firia Ferlania; Ishlahuddin Abdullah; Khairul Umam; Muhammad Azra Arrahman; Dimas Ahmad Iqbal (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2025)
This community service activity aims to provide introduction and basic training in 3D printing technology to the students of SMA Muhammadiyah 10 Sugio, Lamongan. As the Industrial Revolution 4.0 develops, digital manufacturing skills are an important competency that needs to be introduced from the secondary education level. However, there are still many schools that do not have access to this technology, both in terms of devices and understanding of human resources. Therefore, this activity is designed to provide hands-on experience to students through practice-based training. The implementation method includes the delivery of theoretical materials, demonstrations of the use of 3D printers, and the practice of designing and printing simple objects using Inventor design software. This training was attended by 60 students who showed high enthusiasm during the activity. The results of the evaluation showed a significant improvement in the understanding of the concept of 3D printing. In addition, from direct interviews, participants stated that this training was useful and relevant to future needs. This activity not only introduces new technologies to students, but also fosters creativity, design skills, and confidence in developing ideas visually and digitally. It is hoped that this training will be the first step to encourage the adoption of digital fabrication technology in the school environment, as well as an inspiration for other educational institutions to carry out similar activities in improving the technology literacy of the younger generation.